P‐17: New Gate Driver Circuit for Slim‐Border TFT‐LCD Applications. Issue 1 (May 2016) - Lin, Chih-Lung; Lai, Po-Chun; Lee, Ching-En; Chang, Ching-Heng; Wang, Ming-Xun; Du, Yuan-Wei
Abstract : This work presents a new gate driver circuit based on hydrogenated amorphous silicon thin‐film transistors (a‐Si:H TFTs) with simple structure for liquid‐crystal displays (LCDs). The circuit uses the capacitors and colck signals to periodically couple the gate node of the driving TFT to a low voltage level to enhance the stability of the presented gate driver circuit. Moreover, the clock signal drives the pull‐down TFT to suppress the threshold voltage shifts. Simulation results verify that the output waveforms are sequential and uniform. Therefore, the presented gate driver circuit is applicable to slim‐bezel TFT‐LCD applications.